Pengaruh Latihan Olahraga Selam terhadap Kapasitas Vital Paru dan Kebugaran Jasmani pada Horas Diving Club Univesitas Sumatera Utara - Batubara, Bagas Hasonangan; Hasibuan, Sanusi; Simatupang, Nurhayati (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This study aims to determine the effect of diving training on vital lung capacity and the physical fitness of the Horas Diving Club, University of North Sumatra. The research problem is that there has been no checking of the vital lung capacity and physical fitness of divers at the Horas Diving Club, University of North Sumatra. From the data analysis carried out, the results showed that there was a significant influence of diving sports training on the vital capacity of the lungs of Horas Diving Club, North Sumatra University, with the acquisition of the "t" test coefficient, namely count = 4.50 > ttable = 1.833, there was a significant influence of diving sports training on the physical fitness of the Horas Diving Club, North Sumatra University, with the acquisition of the "t" test coefficient, namely tcount = 5.71 > ttable = 1.833. In conclusion, there is influence of diving training on lung capacity and fitness of the Horas diving club training Keywords: Diving Sports Training, Physical Fitness, Vital Lung Capacity ran Jasmani